DISPOSAL OF DRUGS RESIDUES: ANALYSIS OF RECURRING PROBLEMS, AWARENESS AND COLLECTION PROGRAMS - Motz Cid Bezerra, Ana Carolina; Colenci Trevelin, Ana Teresa (Revista Interface Tecnológica, 2020)
This paper brings attention to the problems concerning the consequences of domestic disposal of medicine residues. Contamination by medicines has been identified all over the world, people have their share of responsibility in the process and they must be clarified and involved in the process of raising awareness of waste generation as well as the of the importance of the rational use of medicines, being such use one of the necessary measures to reduce the surplus resulting from unnecessary acquisition or failure to comply with the proposed therapeutic scheme. The research was qualitative, exploratory, and descriptive, involving a case study, which was carried out with 60 university students. Results point to the need for population awareness programs and to the creation of laws in which establishments, such as drugstores and pharmacies, must sell fractional medicines, as an essential measure for reducing the disposal of medicines in the environment.
Keywords: Waste; Contamination; Rational use of medicines